In-depth inhomogeneities in CIGS solar cells: identifying regions for performance limitations by PIXE and EBS - Corregidor, Victoria (2021)
When considering materials to be used as active layers in solar cells, an important required parameter is the proper knowledge of their elemental composition. It should be heavily controlled during growth in order to obtain the desired bandgap and to decrease recombination defects and then increase the solar cell electrical performance. Ion beam analytical techniques and, in particular particle-induced X-ray emission (PIXE) and elastic backscattering spectrometry (EBS), are quite suitable to determine the thickness and composition of such active layers. Furthermore, if these techniques are performed using a nuclear microprobe, lateral and in-depth inhomogeneities can be clearly observed from 2D maps. In many cases, composition variations can be detected from the classical 2D maps obtained from the PIXE spectra. In this work, it is shown how the in-depth variations can also be studied when considering 2D maps reconstructed from the EBS spectra. Such variations are derived from processing conditions and can be related to: i) composition, ii) thickness, iii) roughness, iv) other non-trivial issues. Examples obtained on Cu(In,Ga)Se2 based cells are presented and discussed. Furthermore, the combination of ion beam analytical techniques such as PIXE and EBS is shown to be a competitive and alternative method to those more used and established techniques such as X-ray fluorescence for checking the average composition of the solar cells active layers or SIMS for the determination of elemental depth profile.